(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This study dealt with the process of coating (immersion) and the factors affecting this process stability of the solution and change the time and temperature of immersion. In this study, aluminum alloy (2024-T4) was applied with a solution consisting of zinc oxide and sodium hydroxide (81 g/l NaOH+81 g/l ZnO). Thus, zinc sulphate formed by immersing the sample with nitric acid solution (50 % HNO3+50%water). Then immersed in distilled water. The immersion process was carried out at a different temperature between (25, 55 and 65) °C and different time periods. The results showed an increase in the growth of the deposition layer with increasing duration of the sample and the electrical resistance of the samples and for the same periods. A correlation was drawn between time change and oxide layer growth. Curvature growth was shown with increasing time period for sample exposure to air. The correlation between electrical resistance and time period change was also determined. Simulation between the experimental results and theoretical calculated by using ANSYS version 15. Finally, to confirm the formation and growth of the oxide layer draw by using MATLAB version 15A, Topographic test was examined and XRD.